Consumer debt: Many borrowers unaware of their interest rates; cost display influences likelihood of accepting credit scenario - Antonia Gipp; Jana Samira Hamdan; Lukas Menkhoff (DIW Weekly Report, 2022)
The consumer debt of households in Germany totals in the triple-digit billions and is characterized by a wide range of interest rates. Despite the high volume of debt, many people do not know the terms of their consumer credit contracts. This report analyzes new survey data on general knowledge about typical forms of consumer credit, such as the overdraft facility and consumer loans. Women tend to know less about the interests they pay and are less financially literate. Financial literacy correlates with being informed about interest rates, but is independent of the incidence of consumer debt in general. An experiment reveals respondents are fundamentally price sensitive and that cost display influences the decision to take out consumer credit. For example, there is a significantly higher willingness to take out a consumer loan when the costs are presented per month in euros compared to per year. Consumer protection in financial services should examine these effects, consider them in an evidence-based manner where appropriate, and adjust information disclosure requirements, especially for the overdraft facility. The research findings also support implementing more financial literacy initiatives, especially for women.
Keywords: D18; G51; G53; 330; Household finance; consumer debt; financial literacy